1979
DOI: 10.1002/tera.1420190208
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenic effects of hyperthermia in the bonnet monkey (Macaca radiata)

Abstract: Seventeen timed-mated bonnet monkeys fMacaca radiata) were exposed to hyperthermia in a forced-draft incubator for a duration of one, three, four or eight days between 21 and 46 days of gestation. On each day of exposure the core temperature of the pregnant animal was elevated 2.4 to 5.4OC above the reference temperature recorded before heat exposure. Malformations occurred following a one-hour daily elevation of the core temperature above the reference temperature under the following exposure conditions: 3.Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 10 publications
2
22
0
Order By: Relevance
“…Thus, it seems likely that postnatal behavior and learning capac ity of prenatally heated mice are correlated more closely with their brain weights than with their body weights. The retardation of brain development following maternal heat ing have been reported also in rats [22,23], rabbits [24], and bonnet monkeys [25], Ed wards [26] examined the relationship be tween the body and brain growth of prena tally heated guinea pigs and found that the retardation was more specific for brain de velopment than for general body growth, which contrasts with the effects of undernu trition that produces a greater deficit in gen eral body growth than in brain growth.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, it seems likely that postnatal behavior and learning capac ity of prenatally heated mice are correlated more closely with their brain weights than with their body weights. The retardation of brain development following maternal heat ing have been reported also in rats [22,23], rabbits [24], and bonnet monkeys [25], Ed wards [26] examined the relationship be tween the body and brain growth of prena tally heated guinea pigs and found that the retardation was more specific for brain de velopment than for general body growth, which contrasts with the effects of undernu trition that produces a greater deficit in gen eral body growth than in brain growth.…”
Section: Discussionmentioning
confidence: 96%
“…Intracellular damage, inhibition of mitosis and cellular migration, and cell death may occur after heat exposure [19] . Other mechanisms of cell injury due to heat may involve microvascular lesions [20] , placental necrosis [21] , and infarction [22] . Milunsky et al [23] report that maternal heat exposure in the first trimester of human pregnancy was associated with an increased risk for neural tube defects.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main targets of heat is the developing neural tis sue and therefore mouse embryos are highly susceptible to hyperthermia around the time of neural tube closure. NTDs have been pro duced by heating pregnant animals in other strains of mice [Webster and Edwards, 1984;Finnel et al, 1986], rats [Skreb and Frank, 1963;Edwards, 1968;Germain et al, 1985] , hamsters [Kilham and Ferm, 1976;Umpierre and Dukelow, 1977] and nonhu man primates [Hendrickx et al, 1979], It has been shown that the susceptibility to heat-induced NTDs varies considerably among various strains of mice, suggesting that the sensitivity of the embryo to hyper thermia may be genetically determined [Webster and Edwards, 1984;Finnel et al, 1986] , In the present study, a single heating as brief as 7.5 min at 43.0 °C produced a signif icant number of NTD embryos. A single heating at 42.0 °C was also teratogenic if it is applied for a sufficient duration, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with experimental animals have shown that heat can produce malformations in the rat [Skreb and Frank, 1963;Edwards, 1968;Germain et al, 1985], mouse [Webster and Edwards, 1984;Finnel et al, 1986], hamster [Kilham and Ferm, 1976;Umpierre and Dukelow, 1977], guinea pig [Edwards, 1969a, b;Edwards et al, 1974Edwards et al, , 1984, and nonhuman primate [Hendrickx et al, 1979]. In these animal species, the developing cen tral nervous system, especially the brain, has been most commonly affected.…”
Section: Introductionmentioning
confidence: 99%